2023
DOI: 10.1186/s12967-023-04674-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of various RNA transcripts and construction of biological regulatory networks at the post-transcriptional level for chronic obstructive pulmonary disease

Beibei Li,
Jiajun Zhang,
Hui Dong
et al.

Abstract: Background Although chronic inflammation, oxidative stress, airway remodeling, and protease-antiprotease imbalance have been implicated in chronic obstructive pulmonary disease (COPD), the exact pathogenesis is still obscure. Gene transcription and post-transcriptional regulation have been taken into account as key regulators of COPD occurrence and development. Identifying the hub genes and constructing biological regulatory networks at the post-transcriptional level will help extend current kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…CircRNAs, characterized by their distinct circularized conformations, have emerged as pivotal regulators in a wide range of diseases [ 66 , 67 ]. While recent research advances revealed the dysregulation of certain circRNAs in COPD, only a handful of them have been subjected to functional characterization [ 5 , 68 , 69 ] ( Fig. 2 , Table 3 ).…”
Section: Circular Rnas In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs, characterized by their distinct circularized conformations, have emerged as pivotal regulators in a wide range of diseases [ 66 , 67 ]. While recent research advances revealed the dysregulation of certain circRNAs in COPD, only a handful of them have been subjected to functional characterization [ 5 , 68 , 69 ] ( Fig. 2 , Table 3 ).…”
Section: Circular Rnas In Copdmentioning
confidence: 99%
“…Recent studies have linked a variety of noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) to the occurrence and development of COPD [ 5 ]. Some of these ncRNAs have undergone functional characterization, revealing their potential for early diagnosis and therapeutic intervention in COPD.…”
Section: Introductionmentioning
confidence: 99%